Main tasks and algorithms of wireless network security supporting automated system - Didmanidze Ibraim; Beridze Zebur (Вопросы атомной науки и техники, 2020)
Safety and service quality in wireless networks has recently become an important subject of active research, which is caused by the growing demand for supporting data packages. Without adequate security, organizations avoid using wireless networks. Security issues are an important obstacle for wireless network adaptation. Consequently, security of wireless networks is an important area, which requires reaction, if such networks are widely used. It is necessary for the researchers of this field to identify open problems and to provide relevant solutions to them. Each of such attempts makes the wireless network a bit more secure. The present work aims at the development of a number of measures that would contribute to increasing the safety of wireless networks and through which it would be possible to manage remote workstations.